Physician’s dilemma in treating Acinetobacter baumanii: A combination of art and science - Khadanga, Sagar; Tadepalli, Karuna; Thatoi, Pravat Kumar; Mohanty, Rina; Mohapatra, Namita (Asian Journal of Medical Sciences, 2014)
Acinetobacter are gram negative coccobacilli and ubiquitous in nature1. Quiet frequently they are recovered from inpatients who are hospitalized for prolonged illness and often multiple times. Although originally considered to be a low grade opportunistic pathogen Acinetobacter species has emerged to be one of the common nosocomial pathogen. These isolates are often MDR1. It still remains a physician’s dilemma whether to treat or not such isolates, considering them pathological or commmensals. In one of our case it was isolated as a commensal and the patient did not require any antibiotic. On the hand the second case succumbed just after we started the susceptible antibiotic. DOI: http://dx.doi.org/10.3126/ajms.v6i2.10405 Asian Journal of Medical Sciences Vol.6(2) 2015 105-107